Precision measurement of the top quark mass in lepton + jets final States - Abazov, V M; Abbott, B; Acharya, B S; Adams, M; Adams, T; Agnew, J P; Alexeev, G D; Alkhazov, G; Alton, A; Askew, A; Atkins, S; Augsten, K; et al. (Physical review letters, 2014)
We measure the mass of the top quark in lepton+jets final states using the full sample of pp collision data collected by the D0 experiment in Run II of the Fermilab Tevatron Collider at sqrt[s] = 1.96 TeV, corresponding to 9.7 fb(-1) of integrated luminosity. We use a matrix element technique that calculates the probabilities for each event to result from tt production or background. The overall jet energy scale is constrained in situ by the mass of the W boson. We measure m(t) = 174.98 ± 0.76 GeV. This constitutes the most precise single measurement of the top-quark mass.